2010
DOI: 10.5274/jsbr.47.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Sensitivity of Fusarium Species Associated with Fusarium Diseases to Metconazole, Triticonazole, and Thiabendazole Fungicides

Abstract: Baseline sensitivity was determined using in vitro radial growth assay for Fusarium oxysporum, Fusarium graminearum, and a novel uncharacterized Fusarium sp. nov. from sugarbeet, and F. sambucinum from potato, to metconazole, triticonazole, and thiabendazole. All the isolates from sugarbeet and a thiabendazole-sensitive F. sambucinum isolate were sensitive to the tested fungicides. A thiabendazole-resistant isolate of F. sambucinum was resistant to thiabendazole but sensitive to the other two fungicides. The E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Triazoles are sterol inhibiting fungicides. These fungicides have no immediate effect on the respiratory mechanism; therefore, they do not inhibit spore germination (Siegel, 1981) but are effective at preventing mycelial growth (Burlakoti et al, 2010 most effective control of Fusarium species which has been reported by other studies (Gareis and Ceynowa, 1994;Mesterhazy et al, 2003;Burlakoti et al, 2010;Ruan et al, 2011). Active ingredients of Trifidan is triadimenol, (Hall, 1987) showed that triadimenol reduced neither the incidence of infection of crowns by Fusarium nor the incidence of crown rot and Frank and Ayers (1986) and also Everts and Leath (1993) showed that triadimenol provides control of a foliar pathogen which may cause severe yield loss.…”
Section: Resultsmentioning
confidence: 99%
“…Triazoles are sterol inhibiting fungicides. These fungicides have no immediate effect on the respiratory mechanism; therefore, they do not inhibit spore germination (Siegel, 1981) but are effective at preventing mycelial growth (Burlakoti et al, 2010 most effective control of Fusarium species which has been reported by other studies (Gareis and Ceynowa, 1994;Mesterhazy et al, 2003;Burlakoti et al, 2010;Ruan et al, 2011). Active ingredients of Trifidan is triadimenol, (Hall, 1987) showed that triadimenol reduced neither the incidence of infection of crowns by Fusarium nor the incidence of crown rot and Frank and Ayers (1986) and also Everts and Leath (1993) showed that triadimenol provides control of a foliar pathogen which may cause severe yield loss.…”
Section: Resultsmentioning
confidence: 99%
“…For example, El-Kholy (1999) found that the EC50 values of triticonazole were 1.10 and 0.90 µg mL -1 against mycelial growth of R. solani and F. graminearum, respectively. Also, the EC50 values of triticonazole for isolates of F. graminearum ranged from 0.043 to 4.965 µg mL -1 (Burlakoti et al, 2010). Similarly, carbendazim effectively inhibited the mycelial growth and sclerotial production of R. solani at lower concentration (Sriraj et al, 2014;Kumar et al, 2017).…”
Section: In Vitro Activity Of the Fungicides On The Isolated Fungimentioning
confidence: 99%
“…For example, El-Kholy (1999) found that triticonazole was effective in reducing the Rhizoctonia and Fusarium root rot incidence on wheat plants under greenhouse conditions and increased emergence and plant stands. Burlakoti et al (2010) suggested that triticonazole has the potential to control Fusarium diseases in field conditions if applied in a timely manner. Carbendazim was effective against R. solani at the lowest concentration by maximum inhibiting the mycelial growth and sclerotia formation (Sriraj et al, 2014;Kumar et al, 2017).…”
Section: Separately Effect Of the Tested Fungicides And Bioagents On mentioning
confidence: 99%
See 1 more Smart Citation
“…Eight most virulent isolates: four isolates of F. secorum (525, 408, 605, and 229b), two isolates of F. oxysporum (218 and 581.121), and two isolates of F. graminearum (581.101 and 578.5b) determined in a pathogenicity study [23], were selected and used to screen the cultivars independently under greenhouse conditions. F. secorum was initially reported as F. sp.…”
Section: Isolates and Inoculum Preparationmentioning
confidence: 99%